FP1-4 Factors affecting patient flow in a neurosurgery department. Issue 3 (14th February 2019) - Irvine, S; Chharawala, F; Lawrance, N; Peterson, D; Banerjee, S; Camp, S
Abstract : Objectives: The objectives of this study were to audit the NHS Improvement SAFER patient flow bundle, evaluate the impact of the Red2Green initiative, and assess the impact of frailty on patient flow. Design: A prospective review over a 3 month period. Subjects: All patients admitted to a Neurosurgery Unit from 01/09/2017 to 30/11/2017 were included. Methods: Data were prospectively collected from daily ward lists and patient notes, including demographics, admission/discharge details, length of stay (LOS), expected discharge date, red days with reasons, and frailty (Rockwood Clinical Frailty Scale). NHS Improvement Reference Costs were used for cost analyses. Results: 420 patients (55% elective) were included, total 3909 bed days. All patients received a daily senior review before midday, and EDDs were set at daily MDT meetings. 10% patients were discharged before midday. There were 21% (837) red days, significantly more (76%) for emergency patients (639 vs 198 elective; p<0.001). 63% red days were attributed to awaiting a bed in a local hospital. 25% (106) patients were classed as frail (50 elective), which was associated with a significantly longer LOS (17.3 vs 6; p<0.01), and more red days (615 vs 222; p<0.01). Considering bed costs and lost revenue (with penalties), red days cost is estimated at over £1M per year. Conclusions: SAFER has identified areas for improvement in patient flow, with obvious cost implications. It has created a platform for discussion within the referral network, and identified a role for a geriatric liaison service.